2019
DOI: 10.1016/j.amjcard.2018.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of Hippocampal Atrophy in Patients With Chronic Heart Failure

Abstract: Mild cognitive impairment (MCI) impedes a patient's decision-making ability to support self-care and is associated with increased mortality in patients with chronic heart failure (CHF). Thus, screening for MCI is very important. The assessment of hippocampal atrophy using magnetic resonance imaging can effectively diagnose early MCI. The purpose of this study was to assess the prevalence and prognostic significance of hippocampal atrophy using magnetic resonance imaging in patient with CHF. Of the 491 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…Снижение сердечного выброса, нарушение сократительной функции сердца вызывают ухудшение церебрального кровотока, способствуя формированию и/или прогрессированию когнитивных расстройств (таких как снижение памяти, внимания, интеллекта, замедление психических процессов), которые в последующем могут достигать степени деменции [2,3]. Как правило, пациенты, страдающие ХСН, в меньшей степени соблюдают предписанный режим лечения, что в свою очередь может ухудшать прогноз и выживаемость [4][5][6]. Дислипидемия, а также нарастание тяжести ХСН у пациентов с ИБС могут являться маркерами атрофии гиппокампа, возможно -одной из непосредственных причин развития когнитивного дефицита у этой категории пациентов.…”
Section: Patients With Coronary Artery Disease and Chronic Heart Failunclassified
“…Снижение сердечного выброса, нарушение сократительной функции сердца вызывают ухудшение церебрального кровотока, способствуя формированию и/или прогрессированию когнитивных расстройств (таких как снижение памяти, внимания, интеллекта, замедление психических процессов), которые в последующем могут достигать степени деменции [2,3]. Как правило, пациенты, страдающие ХСН, в меньшей степени соблюдают предписанный режим лечения, что в свою очередь может ухудшать прогноз и выживаемость [4][5][6]. Дислипидемия, а также нарастание тяжести ХСН у пациентов с ИБС могут являться маркерами атрофии гиппокампа, возможно -одной из непосредственных причин развития когнитивного дефицита у этой категории пациентов.…”
Section: Patients With Coronary Artery Disease and Chronic Heart Failunclassified
“…Our findings align with the HSFC report, adding that CI causes distress to patients and that regardless of etiology, it may underpin challenges in selfmanagement and adherence that are often unaccounted for in clinical trials and applied research. 4 As the number of Canadians living with heart disease grows rapidly and in parallel with improvements in cardiac treatment that extend survival, finding ways to address these issues is ever more critical. The HSFC report and our own survey results reveal that CI and its long-term effects on individuals with HF are an independent outcome worthy of study.…”
Section: To the Editormentioning
confidence: 99%
“…These extracardiac CNS disorders include the development or aggravation of existing cognitive dysfunction. [1][2][3][4][5][6] Our previous studies demonstrated the signifi cant correlation between the severity of chronic heart failure (CHF) and functional (cognitive functions) and morphological (temporal, parietal, and occipital gray matter thickness, middle cerebellar peduncle width, and diffusion of the water molecules) status of the central nervous system. [7][8][9] In modern cardiology, functional class (FC) and left ventricular ejection fraction (LVEF) are the most commonly used parameters to determine the severity of CHF.…”
Section: Introducionmentioning
confidence: 99%